Advances in Marine Chitin and Chitosan II, 2017 - Hitoshi Sashiwa (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
As a result of our call in 2014 for submissions to a Special Issue, Advances in Marine Chitin and Chitosan in Marine Drugs, we are now pleased to tell you that this issue has been published. Twenty high class papers were included in this issue, which we now plan to publish as a book. In addition we now seek to publish a further Special Issue, Advances in Marine Chitin and Chitosan II, 2017, in Marine Drugs. As before, we plan to produce a strong, very exciting issue that will encompass breakthroughs in high value, scientific and industrial chitin and chitosan research. Despite significant advances in chitin and chitosan research since the 1970s, current overviews in recent publications involving chitin and chitosan research advances need reporting.